2016
DOI: 10.1245/s10434-016-5206-3
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram to Predict Brain Metastases of Resected Non-Small Cell Lung Cancer Patients

Abstract: The nomogram developed in this study demonstrated its discrimination capability for predicting 3- and 5-year occurrence of brain metastases, and can be used to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…A multicenter retrospective study showed a high serum NSE level was an independent determinant of poor survival in patients with NSCLC with BM . NSE was identified as a significant predictive factor based on the stage I‐III NSCLC‐resected patients in the study by Zhang . In Ji's study, increased NSE and CA125 levels are both independent risk factors for BM .…”
Section: The Levels Of Tumor Markersmentioning
confidence: 94%
See 2 more Smart Citations
“…A multicenter retrospective study showed a high serum NSE level was an independent determinant of poor survival in patients with NSCLC with BM . NSE was identified as a significant predictive factor based on the stage I‐III NSCLC‐resected patients in the study by Zhang . In Ji's study, increased NSE and CA125 levels are both independent risk factors for BM .…”
Section: The Levels Of Tumor Markersmentioning
confidence: 94%
“…For operable NSCLC, the incidence of brain metastases in patients with adenocarcinoma was 2.86 times higher than that in non‐adenocarcinoma patients (95% CI: 1.58‐5.16, P = 0.001) . Adenocarcinoma was also reported to be one of the predictive factors for BM (RR: 3.39; 95% CI: 1.78‐6.46 and P = 0.0002) in a group of stage I‐III NSCLC patients .…”
Section: Pathologymentioning
confidence: 96%
See 1 more Smart Citation
“…Several trials have shown that PCI is effective in reducing brain metastasis for NSCLC patients; however, there is no survival advantage [7]. The effort to identify lung cancer patients with high risk for developing brain metastasis would be able to avoid excessive treatment for patients with less aggressive tumors and increase the benefits of PCI [8, 9]. In addition, the identification of high risk patients for developing brain metastasis could also be used to establish an optimal follow-up strategy for detecting brain relapse.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of this approach in the management of non-small cell lung cancer (NSCLC) patients is still in doubt [7]. Hence, defining the predictive factors for brain metastasis development and identifying high risk lung adenocarcinoma patients who will benefit from PCI is meaningful [810]. …”
Section: Introductionmentioning
confidence: 99%